Treatment of Accommodative and Vergence Dysfunction in Traumatic Brain Injury (TBI): A Case Report. - Griffith, Anna (Optometry & Visual Performance, 2015)
Background: Accommodative insufficiency (AI), accommodative infacility, and convergence insufficiency (CI) are some of the most common visual problems following traumatic brain injury (TBI). In light of the increased prevalence of TBIs in modern-day combat, it is important for clinicians to be aware of the associated visual symptoms and methods of treatment. The mechanism of progressive neural damage in TBI as well as the neural-anatomical pathways of accommodation and vergence will be reviewed in the case report presented here. Important considerations when treating patients with TBI will also be discussed. Case Report: This case report describes the diagnosis, management, and treatment of accommodative and vergence dysfunction in a 33-year-old veteran with a history of multiple TBIs incurred during combat in Afghanistan. The veteran was diagnosed with asymmetric accommodative insufficiency and infacility and gross convergence insufficiency, and he had decreased depth perception. Five in-office vision therapy sessions were conducted over the course of a month and a half, with daily practice at home, followed by maintenance activities and tapering of vision training. Treatment restored the patient's visual clarity, comfort, and fine stereopsis, enabling him to pursue his goal of returning to school for engineering. Conclusion: Vision therapy improves visual function and symptoms from TBI in many patients. An increase in TBI due to modern-day warfare has increased the awareness of and the need for recognition and treatment of visual problems. Most, if not all, communities have a need for vision care for patients with TBI from car crashes, accidents, sports injuries, and concussion. Prompt diagnosis and treatment of visual dysfunction is critical to improving quality of life, ability to work towards vocational goals, and progress of other rehabilitation therapies which require varied visual tasks.